Increase in GLBTQ Minority Stress Following the 2016 US Presidential Election. Issue 1 (15th March 2018) - Gonzalez, Kirsten A.; Ramirez, Johanna L.; Galupo, M. Paz
ABSTRACT: Since his inauguration, Donald J. Trump and his presidential administration have failed to show support or publicly acknowledge the rights of gay, lesbian, bisexual, transgender, and queer (GLBTQ) individuals. Historically, conservative anti-GLBTQ campaigns and policies have caused long-lasting negative effects on GLBTQ individuals' mental health, physical health, and sense of safety in their communities. The current presidential administration has done little to mitigate these effects and has taken steps since Trump's inauguration to continue a conservative pattern of anti-GLBTQ initiatives. This study assessed 172 GLBTQ individuals' perceptions of minority stress experiences before and after the 2016 US presidential election. Paired-sample t -tests indicated that participants experienced significantly higher levels of stress pertaining to sexual orientation rumination, daily experiences of harassment/discrimination, more symptoms of depression and anxiety post-election, as well as a stronger connection to the GLBTQ community. An exploratory regression analysis confirmed that sexual-orientation-based rumination, sexual identity salience, and daily experiences of distal discrimination were adequate predictors of sexual minorities' levels of vigilance post-election. Discussion focuses on the impact of the Trump administration on minority stress experiences and the well-being of GLBTQ Americans. Implications of this study point to the need to continue to explore how to best support and bolster GLBTQ well-being during anti-GLBTQ political administrations.